Divinity and maximal greatness - Hill, Daniel J., 1972- (Routledge studies in the philosophy of religion, 2005)
This book examines divine nature in terms of maximal greatness. It investigates each attribute associated with maximal greatness - omnipotence, omniscience, perfect goodness and beauty, arguing that maximal greatness is necessary for divinity.